-1(-4z-5)-2=2(2z+5)-6

Simple and best practice solution for -1(-4z-5)-2=2(2z+5)-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -1(-4z-5)-2=2(2z+5)-6 equation:



-1(-4z-5)-2=2(2z+5)-6
We move all terms to the left:
-1(-4z-5)-2-(2(2z+5)-6)=0
We calculate terms in parentheses: -(2(2z+5)-6), so:
2(2z+5)-6
We multiply parentheses
4z+10-6
We add all the numbers together, and all the variables
4z+4
Back to the equation:
-(4z+4)
We get rid of parentheses
-1(-4z-5)-4z-4-2=0
We add all the numbers together, and all the variables
-4z-1(-4z-5)-6=0
We move all terms containing z to the left, all other terms to the right
-4z-1(-4z-5)=6

See similar equations:

| 38.95-11.98=p | | 40=2x(x-4)(x-1) | | M4+m8=12 | | 9p+10=-9+10p+9 | | -6p+5=-7-9p | | X²+12x-32=0 | | x-45=120 | | -8-7h=-8h+2 | | -8b+86=2b-4 | | 91+150+105+3x+2x+x=720 | | 8y+10=-10+5y-10 | | -8b+86=2b-5 | | −21/2b=61/4 | | -125=-5(-4p+5) | | 60y=60y | | x-45=130 | | 1/2n=31/4 | | 48+m=-34 | | -9p+1-2p=-10p+10 | | 0.5n=3.25 | | 99=7(r+8)+1 | | W=7796/w | | 5x+(9x2)=13 | | 3t+5=-9t+10t | | 6x+x+8=80 | | 2.1j-9.22=2+8.7j | | 3x-29=7(x+3) | | 3x+x2x=15 | | 7m-8=4m+10 | | 2x-95=47 | | 1-4f=-10-6f-9 | | 5*x=3000000 |

Equations solver categories